Light element discontinuities suggest an early termination of star formation in the globular cluster NGC 6402 (M14). Issue 3 (1st March 2019) - Johnson, Christian I; Caldwell, Nelson; Michael Rich, R; Mateo, Mario; Bailey, John I
ABSTRACT: NGC 6402 is among the most massive globular clusters in the Galaxy, but little is known about its detailed chemical composition. Therefore, we obtained radial velocities and/or chemical abundances of 11 elements for 41 red giant branch stars using high resolution spectra obtained with the Magellan-M2FS instrument. We find NGC 6402 to be only moderately metal-poor with 〈[Fe/H]〉 = −1.13 dex (σ = 0.05 dex) and to have a mean heliocentric radial velocity of −61.1 km s −1 (σ = 8.5 km s −1 ). In general, NGC 6402 exhibits mean composition properties that are similar to other inner Galaxy clusters, such as [α/Fe] ∼+0.3 dex, [Cr, Ni/Fe] ∼ 0.0 dex, and 〈[La/Eu]〉 = −0.08 dex. Similarly, we find large star-to-star abundance variations for O, Na, Mg, Al, and Si that are indicative of gas that experienced high temperature proton-capture burning. Interestingly, we not only detect three distinct populations but also find large gaps in the [O/Fe], [Na/Fe], and [Al/Fe] distributions that may provide the first direct evidence of delayed formation for intermediate composition stars. A qualitative enrichment model is discussed where clusters form stars through an early ( 5–10 Myr) phase, which results in first generation and 'extreme' composition stars, and a delayed phase ( 40 Myr), which results in the dilution of processed and pristine gas and the formation of intermediate composition stars. For NGC 6402, the missing intermediate composition stars suggest the delayed phase terminated prematurely, and as a result the cluster may uniquely preserve details of the chemical enrichment process.